A Simplified ALE model for finite element simulation of ballistic impacts with bullet splash – development and experimental validation - Riccardo Andreotti (Gruppo Italiano Frattura, 2021)
An original simplified finite element model is proposed to simulate the effects of non-penetrating ballistic impacts causing the so-called bullet splash phenomenon (complete bullet fragmentation), while no fragmentation is caused to the target. The model is based on the Arbitrary Lagrangian Eulerian formulation (ALE) and it simulates the impact as a fluid-structure interaction. The bullet splash phenomenon has been tested by experimental analyses of AISI 304L plates impacted by 9x21 FMJ (full metal jacket) bullets. The model has been developed with the aim of creating a simplified approach to be used in the industry and forensic sciences to simulate the non-penetrating interaction of soft impactors with hard targets. Comparisons between evidence and simulation results lead to the conclusion that the proposed approach can be used in a conservative way to estimate both local and global effects of bullet-splash phenomena.